PENGARUH MODEL PEMBELAJARAN PERMAINAN MODISCO BALL TERHADAP KETERAMPILAN PASSING DALAM PERMAINAN SEPAKBOLA - Jaka Jaka (STKIP Muhammadiyah Kuningan, 2022)
The Influence of the Modisco Ball Game Learning Model on Passing Skills in Football Games" in fifth grade students of SD Negeri 2 Ancaran. The purpose of this study was to produce a soccer learning model in the form of a modisco ball game to overcome students lack of activity and interest and to form modifications according to the characteristics of fifth grade students of SD Negeri 2 Ancaran in physical education learning. This study uses a field experiment method. The population and sample of this study were the fifth grade students of SD Negeri 2 Ancaran, totaling 29 people. The results of the analysis and processing of the pre-test data obtained the lowest score of 3 and the highest score of 7. While the post-test data obtained the lowest score of 6 and the highest score of 11, the average pre-test result was 8.5 and post-test of 16.03 there is an increase of 7.53. Thus, based on the table of paired samples t-test, it is known that the value of sig (2-tailed) is 0.000. Because the value of sig ( 2-tailed ) 0.000 < 0.05 , thus is rejected and is accepted. This means that there is an increase in the passing of fifth grade students of SD Negeri 2 Ancaran in the learning of modisco ball